Hydrogels Containing Budesonide-Loaded Nanoparticles to Facilitate Percutaneous Absorption for Atopic Dermatitis Treatment Applications - Campos, Estefânia V. R.; Proença, Patricia L. F. [UNESP]; Costa, Tais Germano Da; De Lima, Renata; Hedtrich, Sarah; Fraceto, Leonardo Fernandes [UNESP]; De Araujo, Daniele Ribeiro (American Chemical Society (ACS), 2021)
Atopic dermatitis (AD) is a chronic, relapsing inflammatory skin disorder characterized by intense itching and recurrent eczematous lesions. Topical corticosteroids are the first-line treatment to control moderate-to-severe AD; however, prolonged application of corticosteroids is required, which can result in dermal atrophy as a side effect. Drug-delivery systems can provide more effective and targeted therapy strategies. In this study, budesonide (BUD) was encapsulated into chitosan (CS)-coated PLGA nanoparticles, which were further incorporated into poloxamer hydrogels to improve the anti-inflammatory activity and decrease adverse effects. The nanoparticles were prepared by the emulsification-solvent evaporation technique, and their physicochemical characteristics were evaluated. Rheological properties of the hydrogels, such as viscosity and sol-gel transition temperature, were evaluated with and without nanoparticles. In vitro release kinetics and ex vivo drug absorption studies were performed using Franz diffusion cells. The nanoparticles showed a mean diameter of 324 ± 4 nm, positive ζ potential (20 mV) due to CS coating, and high encapsulation efficiency (>90%). The nanoparticles did not show cytotoxic effects in primary human fibroblasts and keratinocytes; however, all formulations induced the generation of reactive oxygen species. Both nanoparticles and hydrogels were able to change the release kinetics of BUD when compared to the nonencapsulated compound. Nanoparticles were not able to surmount the stratum corneum of excised human skin, but the nanoencapsulation facilitated the skin absorption of BUD. The hydrogels containing nanoparticles or not showed non-Newtonian and pseudoplastic behavior. The nanoformulations seem to be a good candidate to deliver glucocorticoids in the skin of AD patients.
Keywords: atopic dermatitis; budesonide; polymeric nanoparticles; thermoresponsive hydrogels; topical release